CRITICAL THINKING IN ADOLESCENTS - Karshibaeva , D.; Sattarova , F. (EurasianUnionScientists, 2021)
This article discusses the issue of critical thinking elements that are formed in childhood and increase in adolescence. It will teach the student to avoid difficult situations and not be afraid to Express themselves.